إدارة التميز ودوره في تحسين مستوى جودة الخدمة المقدمة للعملاء: دراسة تطبيقية على القطاع المصرفي - حسين، رامز رمضان محمد (الجمعية المصرية للاقتصاد السياسي والإحصاء والتشريع, 2020)
هدفت هذه الدراسة إلى تحديد أثر تطبيق عوامل ومبادئ التميز الإداري (القيادة - السياسات والاستراتيجية - الموارد البشرية - رضا المستفيدين "العملاء") على تحسين مستوى جودة الخدمة المقدمة للعملاء في البنوك العامة بجمهورية مصر العربية ولهذا الغرض تم تصميم استمارة استقصاء تكونت من (٤٠) عبارة وقد تم استخدام أسلوب العينات "العينة العشوائية" وذلك لكبر حجم المجتمع وقد تم توزيع استمارة الاستقصاء على كل من يعمل في الوظائف الإشرافية والقيادية في تلك البنوك حيث تم توزيع عدد (٢٠٠) استمارة تم استرداد منها عدد (١٨٣) استمارة كان منها (١٧٦) استمارة صالحة لإجراء التحليل الإحصائي أي ما نسبته (88%) من إجمالي عدد الاستمارات الموزعة وقد اعتمدت هذه الدراسة على المنهج الوصفي التحليلي بالإضافة إلى أسلوب الدراسة الميدانية لجمع البيانات اللازمة لإتمامها وقد تم استخدام برنامج التحليل الإحصائي (SPSS) في تحليل بيانات الدراسة واختبار فرضيتها حيث تم استخدام الإحصاء الوصفي لعرض أسئلة الدراسة كما تم استخدام اختبارات التوزيع الطبيعي وتحليل الانحدار البسيط لاختيار فرضياتها. وقد توصلت الدراسة إلى مجموعة من النتائج من أهمها: أن البنوك العامة محل الدراسة ترى أن تطبيق عوامل ومبادئ التميز الإداري (القيادة - السياسات والاستراتيجية - الموارد البشرية - رضا المستفيدين "العملاء") تساعد على تحسين مستوى جودة الخدمة المقدمة للعملاء من تلك البنوك وقد أوصت الدراسة في نهايتها بضرورة تبني البنوك العامة محل الدراسة عوامل التميز الإداري في إدارة أعمالها الإدارية.
The present study aims at determining the impact of implementing the factors and principles of excellence management (leadership, policies and strategies, human resources, customer satisfaction) to improve the customer service quality in public banks of Egypt. For this purpose, the current study employs a 40-question questionnaire and due to the huge size of the Egyptian society, the sampling method is applied randomly. This questionnaire is distributed to all those who work in supervision and leadership positions in these public banks. According to the study, 200 forms are distributed, of which 183 forms are retrieved, of which 176 forms are valid for conducting the statistical analysis, i.e. 88% of the total number of the distributed forms. The study depends on the oescriptive analytical approach and the pilot study methodology. It also uses the statistical analysis program (SPSS) to analyze the data and test their hypotheses while the descriptive statistics is used to refer to the questions of the study. The normal distribution tests are used to analyze the simple declination in order to choose their hypotheses as well. The study concludes to a number of results. One of the important results is that the national banks of the study believe that the application of the factors and principles of excellence management (leadership, policies and strategies, human resources, customer satisfaction) helps to improve the customer service quality in these banks. Finally, the study then recommends that national banks of the study should adopt the factors and principles of excellence management in their administrative businesses.
Keywords: إدارة التميز -- الخدمات المصرفية -- جودة الخدمات -- إدارة الجودة الشاملة